Analysis of Factors Affecting Trust on the Use of FinTech (P2P Lending) in Indonesia - Jimmy Pratama (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2021)
Since 2016 the P2P Lending industry has begun to develop in Indonesia. Peer to Peer Lending (P2P Lending) is a new alternative to getting funds in the form of money loans to individuals or investors. Fintech P2P Lending provides convenience through a simple and fast service. Its features can be accessed by anyone, anytime, anywhere. On the other hand, investors or lenders have investment alternatives with attractive returns. So that it quickly spread to all segments of Indonesian society. The purpose of this research is to analyze what factors can influence trust in using of P2P Lending in Indonesia. The difference between this study and previous research is that there is no research that focuses on trust in the use of FinTech, especially P2P Lending in Indonesia. This research is a type of quantitative research that used is primary data obtained by distributing questionnaires directly to Indonesians. The samples taken by Simple Random Sampling Technique and obtained 400 respondents as user fintech. And the statistical analysis used in this study is multiple regression and using SPSS 23 program. Based on the result, this study showed that the variable of structural assurance, easy of use, and brand image were significant on trust in using FinTech, meanwhile the variable of  integrity was not significant on trust in using FinTech.